Le Traitement Antibiotique Dans La Pédiatrie - Stoyan Papanov; Ekaterina Petkova; Zlatka Dimitrova; Vania Georgieva; Kalin Ivanov; Stanislava Ivanova; Rumen Mladenov (European Scientific Journal, ESJ, 2016)
The current study should be paid extra attention because antibiotics are main cluster of drugs for treatment of child infections and illnesses. They are the most commonly prescribed medicines for children, relatively expensive and consume 60-70% of the budget for treatment of child illnesses, with exclusion only in malign sickness. OBJECT: The current study represents common classification of antibiotics and the most commonly used antimicrobial agents during childhood. RESEARCH METHODS - Systematic approach and critical analysis of the available scientific periodicals - Interview method of the survey (survey data pediatricians and general practitioners in the region of Plovdiv, Bulgaria.) - Own research on the issue. RESULTS AND DISCUSSION: Most often, doctors use: Broad-spectrum penicillins: Amoxicillin, Amopen, Ospamox, Duomox First generation cephalosporins: Ospexin, Cephalexin Second-generation cephalosporins: Cefaclor Third generation cephalosporins: Abricef, Cefotaxime, Rocephin, Fortum Fourth generation cephalosporins: Maxipime Macrolides: Macropen Aminoglycosides: Gentamicin, Amicacine CONCLUSION: No significant differences are observed in the prescribed by the general practitioners and pediatricians antibiotics.